CHARACTERISTICS OF THE SHARIA SUPERVISORY BOARD AND ITS RELEVANCE TO ISLAMIC SOCIAL REPORTING AT ISLAMIC BANKS IN INDONESIA - Inten Meutia; Desi Aryani; Sari Mustika Widyastuti (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2019)
This study was conducted to examine the effect of the size of the Sharia Supervisory Board (DPS), the number of DPS meetings, DPS education, and duality in SSB positions on Islamic Social Reporting using the control variable of company size and profitability. The object of the study consisted of 13 Sharia Commercial Banks and 21 Sharia Business Units recorded in the Financial Services Authority in the 2015 2017 period. Content Analysis is used to identify themes and items in the bank's annual report. Multiple linear regression analysis is a method used in the data processing. This study proves the variable number of SSB meetings, duality in SSB positions, SSB size and profitability significantly influence ISR Islamic Social Reporting. Meanwhile, the variable number of SSB and SSB education was found to have no significant effect on Islamic Social Reporting.Key words : Sharia Supervisory Board, Islamic Bank, Islamic Social Reporting